Group 1st of Non-pharmacological Therapy that Most Effective to Increase Hemoglobin in Pregnancy - Abdullah, Ikhwan; Widia Shofa Ilmiah; Prihatono, Amal; Candra Kurniawan, Leny (Universitas Airlangga, 2024)
Background: Anemia of pregnancy is still a global problem. The prevalence rate of anemia in pregnancy in developed countries at 14% and in developing countries at 51%, in Asian countries at 33.3%, Brunei Darussalam at 28.0%, Thailand at 30%, the Philippines at 32.3%, Malaysia at 26.6%, Singapore at 28.5%, and Vietnam at 23.5%. The prevalence of anemia in pregnant women in Indonesia in the 1st trimester at 3.8%, the 2nd trimester at 13.6% and the 3rd trimester at 24.8% Indonesian women die every year due to pregnancy and childbirth, while in East Java at 40%. The cause of anemia during pregnancy is nutritional deficiencies, especially lack of iron, folate, and vitamins. Aims: To determine the level of effectiveness of non pharmacology therapy to increase hemoglobin in pregnancy. Methods: Systematic review using PRISMA and PICO methods. The population of this study is all international journals and accredited national journals sinta 1-6 totaling 87 articles. The sample is 23 articles that are appropriate with the inclusion criteria. The data collection is conducted by searching research articles in the database which including Google, GoogleScholar, Research Gate, NCBI, Science Direct, SAGE, Elsevier, and Sinta. Analysis is use thematic analysis. Results: The 1st group of non pharmacology therapy can increase hemoglobin levels, namely yellow pumpkin seeds, papaya fruit, papaya leaf juice, an avocado juice, red spinach juice, sweet potato leaf decoction, red guava, roselle tea, fried catfish, green bean juice, boiled chicken eggs, soy milk, honey, 2nd group, namely moringa leaf extract, chickpeas, dates, Dutch eggplant juice, ambon bananas, 3rd group, namely katuk leaf, beets, acupuncture points SP3, LR3, KI3, red seaweed, red dragon fruit. Conclusion: The most effective non pharmacology therapy for increasing hemoglobin in pregnancy is non pharmacology therapy in 1st group.